Enhanced Recovery After Surgery (ERAS) pada Pediatrik yang Menjalani Operasi Kolorektal - Pratomo, Bhirowo Yudo; Widyastuti, Yunita; Ilman, Pesiar (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Enhanced recovery after surgery (ERAS) was first described by Henrik Kehlet as a tool for optimizing perioperative care. The general scope of ERAS includes perioperative counseling, limiting the fasting hours before surgery, postoperative enteral intake, early mobilization, use of non-opioid pain medications, and restriction of intravenous fluids, drainage, and catheters. Colorectal surgery in pediatrics has a higher infection rate in the surgical area than in adults, thereby the implementation of ERAS in this operation canhave a big impact. There are few studies on the implementation of ERAS in pediatrics. Despite that, the available data shows the implementation of ERAS in pediatrics undergoing colorectal surgery is positive.